The role of ethnicity in Kenya's transition from single party rule to political pluralism (1992-2007) - Godwin, Shilaho Westen Kwatemba (My University, 2012)
The thesis attempts to explain the salience of ethnicity in political party formation and the cyclic ethnic violence during elections in Kenya’s multiparty democracy. It accords special focus on how ethnicity was deployed in the management and even disorganisation of politics in Kenya’s multiparty era. The thesis examines two significant questions. Why and how ethnicity was salient in Kenya’s transition from one-party rule to political pluralism? What was the relationship between ethnic conflict and political liberalization in Kenya? The thesis contributes to our understanding of Kenya’s attempt at transition from authoritarianism to more democratic forms of politics and its impact on multiparty politics in Kenya’s multiethnic society. It also illuminates the trajectories that Kenya's politics has taken since the advent of multiparty politics in the early 1990s. The thesis considers the significance of the concept of democratic transition in the context of Kenya, a country emerging from single party rule characterised by authoritarianism and patron-client politics. It locates the protracted transition process in the immediate post-independence exclusionary politics along ethnic lines and the resultant fall out among the political elite. The thesis presents ethnicity as a lived experience that had politicised Kenya’s multiethnic society. The centrality of ethnicity in Kenyans’ lives is testified to by the views by respondents from a mosaic of ethnic, social economic and political strata.
Ph.D. University of the Witwatersrand, Faculty of Humanities and Social Sciences, 2012